Chemical and Toxicological Evolution of Carbon Nanotubes During Atmospherically Relevant Aging Processes - Liu, Yongchun; Liggio, John; Li, Shao-Meng; Breznan, Dalibor; Vincent, Renaud; Thomson, Errol M.; Kumarathasan, Premkumari; Das, Dharani; Abbatt, Jonathan; Antinolo, Maria; Russell, Lynn (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2015)
The toxicity of carbon nanotubes (CNTs) has received significant attention due to their usage in a wide range of commercial applications. While numerous studies exist on their impacts in water and soil ecosystems, there is a lack of information on the exposure to CNTs from the atmosphere. The transformation of CNTs in the atmosphere, resulting in their functionalization, may significantly alter their toxicity. In the current study, the chemical modification of single wall carbon nanotubes (SWCNTs) via ozone and OH radical oxidation is investigated through studies that simulate a range of expected tropospheric particulate matter (PM) lifetimes, in order to link their chemical evolution to toxicological changes. The results indicate that the oxidation favors carboxylic acid functionalization, but significantly less than other studies performed under nonatmospheric conditions. Despite evidence of functionalization, neither O-3 nor OH radical oxidation resulted in a change in redox activity (potentially giving rise to oxidative stress) or in cytotoxic end points. Conversely, both the redox activity and cytotoxicity of SWCNTs significantly decreased when exposed to ambient urban air, likely due to the adsorption of organic carbon vapors. These results suggest that the effect of gas-particle partitioning of organics in the atmosphere on the toxicity of SWCNTs should be investigated further.